Skip to main content

Resta de Fracciones-Soluciones


\frac{1}{2}-\frac{1}{3}-\frac{1}{4}

 

  • \frac{1}{2}-\frac{1}{3}-\frac{1}{4}=\left ( \frac{1}{2}-\frac{1}{3} \right )-\frac{1}{4}

 

  • \frac{1}{2}-\frac{1}{3}=\frac{3}{2\cdot 3}-\frac{2}{3\cdot 2}=\frac{1}{6}

 

  • \frac{1}{6}-\frac{1}{4}=\frac{4}{6\cdot 4}-\frac{6}{4\cdot 6}=-\frac{2}{24}=-\frac{1}{12}

 

3-\frac{2}{3}-\frac{x}{2}

 

  • 3-\frac{2}{3}-\frac{x}{2}=\left ( \frac{3}{1}-\frac{2}{3} \right )-\frac{x}{2}

 

  • \frac{3}{1}-\frac{2}{3}=\frac{9}{1\cdot 3}-\frac{2}{3\cdot 1}=\frac{7}{3}

 

  • \frac{7}{3}-\frac{x}{2}=\frac{14}{3\cdot 2}-\frac{3x}{2\cdot 3}=\frac{14-3x}{6}

 

\frac{z^{2}}{3}-\frac{z^{2}}{x}

 

  • \frac{z^{2}}{3}-\frac{z^{2}}{x}=\frac{xz^{2}}{3\cdot x}-\frac{3z^{2}}{x\cdot 3}=\frac{z^{2}\left ( x-3 \right )}{3x}